2019
DOI: 10.1111/psyg.12481
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effect of aroma oil as a bath salt on cognitive function

Abstract: Background Aromatherapy is a non‐pharmacological therapy for the improvement of dementia symptoms. This study aimed to assess the effects of aroma oil as a bath salt on cognitive function, olfactory function and sleep quality. Methods This was a randomised controlled trial. Overall, 49 patients were able to provide consent, and 35 were finally analysed (Alzheimer's disease: 10, mild cognitive impairment: 25). The patients were randomly assigned to use 0.1%, 0.5% or 1% aroma bath salt. During daily bathing, bat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…(Myristicaceae), and Crocus sativus L. (Iridaceae) has been traditionally recommended for the treatment of memory loss in Iranian traditional medicine (ITM) [ 19 ]. On the other hand, non-pharmacological approaches have been developed for the improvement of cognitive problems [ 20 , 21 ] and in this respect, aromatherapy has been widely considered as a strong tool [ 22 ]. In different studies, the combination of therapies has depicted significant results in improving memory, quality of life, and treatment of other complications in patients with AD [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…(Myristicaceae), and Crocus sativus L. (Iridaceae) has been traditionally recommended for the treatment of memory loss in Iranian traditional medicine (ITM) [ 19 ]. On the other hand, non-pharmacological approaches have been developed for the improvement of cognitive problems [ 20 , 21 ] and in this respect, aromatherapy has been widely considered as a strong tool [ 22 ]. In different studies, the combination of therapies has depicted significant results in improving memory, quality of life, and treatment of other complications in patients with AD [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Kouzuki et al. ( 2020 ) reported minor dermatological side effects following the use of bath salts. No significant adverse events were reported across the remaining included studies.…”
Section: Resultsmentioning
confidence: 99%
“…Kouzuki et al. ( 2020 ) conducted a randomised controlled trial of aroma oil as a bath salt, to determine its effect on cognition, olfactory function and subjective measures of sleep as determined by PSQI‐J (Japanese version of PSQI). 35 participants with MCI or AD were randomised to three strengths of aroma oils (0.1%, 0.5% and 1%) with bathing performed nightly after 18:00 hr for 24 weeks.…”
Section: Resultsmentioning
confidence: 99%
“…However, a study in individuals with MCI and dementia found no improvement in any measured outcomes, including sleep and cognition. 94 There are very few investigations in individuals with MCI and evidence in dementia is conflicting and of low-quality. 95 There is no convincing evidence to date that aromatherapy has an impact on NPS in MCI.…”
Section: Sensory Stimulationmentioning
confidence: 99%